Mechanisms of metabolic memory and renal hypoxia as a therapeutic target in diabetic kidney disease. Issue 3 (13th March 2017) - Hirakawa, Yosuke; Tanaka, Tetsuhiro; Nangaku, Masaomi
Abstract : Diabetic Kidney Disease is a notion which includes Diabetic Nephropathy. Metabolic memory plays a crucial role in the progression of various complications of diabetes, including DKD. Hypoxia and oxidative stress are appropriate targets of therapies against DKD via alteration of metabolic memory. Abstract: Diabetic kidney disease (DKD) is a worldwide public health problem. The definition of DKD is under discussion. Although the term DKD was originally defined as 'kidney disease specific to diabetes, ' DKD frequently means chronic kidney disease with diabetes mellitus and includes not only classical diabetic nephropathy, but also kidney dysfunction as a result of nephrosclerosis and other causes. Metabolic memory plays a crucial role in the progression of various complications of diabetes, including DKD. The mechanisms of metabolic memory in DKD are supposed to include advanced glycation end‐products, deoxyribonucleic acid methylation, histone modifications and non‐coding ribonucleic acid including micro ribonucleic acid. Regardless of the presence of diabetes mellitus, the final common pathway in chronic kidney disease is chronic kidney hypoxia, which influences epigenetic processes, including deoxyribonucleic acid methylation, histone modification, and conformational changes in micro ribonucleic acid and chromatin. Therefore, hypoxia and oxidative stress are appropriate targets of therapies against DKD. Prolyl hydroxylase domain inhibitor enhances the defensive mechanisms against hypoxia. Bardoxolone methyl protects against oxidative stress, and can even reverse impaired renal function; a phase 2 trial with considerable attention to heart complications is currently ongoing in Japan.